Effective length of a single long horizontal ground conductor buried in homogeneous soil - Wan Ahmad, Wan Fatinhamamah; Thomas, David W. P.; Christopoulos, Christos; Chong, Siang Tee; Jasni, Jasronita; Ab Kadir, Mohd Zainal Abidin; Hizam, Hashim (IEEE, 2009)
The effectiveness of a grounding system is highly dependent on several parameters such as its size, i.e. the length of the ground conductor, the electrical characteristics of the ground conductor and its surrounding soil. A single long horizontal ground conductor being a basic configuration of a grounding system could act as a path for the transient currents to be easily and effectively dissipated into the earth. This study is to investigate the effective length and transient responses along a single long horizontal ground conductor based on a distributed parameters using TLM. The length of the ground conductor is segmented to assess the characteristics variations of the transient behavior against high transient such as lightning strike. It is found that a ground conductor with an effective length of 150 m is effective in dissipating transient currents into its surrounding homogenous soil.